2007
DOI: 10.1007/s15010-007-6353-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS on Avian Influenza Preparedness in Healthcare Workers

Abstract: Healthcare workers who had been actively involved in SARS work were more "positive" in responding to the impending avian influenza epidemic. Whether the level of preparedness can be sustained would need to be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 12 publications
5
63
3
Order By: Relevance
“…Twenty-two studies reported the ethical clearance of their study. [3][4][5][6]13,15,20,[22][23][24][25][26][27]29,[31][32][33][35][36][37][39][40] Nurses in the ''post-SARS'' group were more willing to provide care for patients with SARS and agreed more with the general SARS control measures than those in the ''during-SARS'' group . The nurses' levels of agreement with general SARS infection control measures and the need for quarantine after providing care for infected patients were significant predictors of nurses' commitment to their professional obligation. 2004 Gullion 14 20.2% of respondents were not at all willing to care for a patient infected with a communicable respiratory infection such as SARS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty-two studies reported the ethical clearance of their study. [3][4][5][6]13,15,20,[22][23][24][25][26][27]29,[31][32][33][35][36][37][39][40] Nurses in the ''post-SARS'' group were more willing to provide care for patients with SARS and agreed more with the general SARS control measures than those in the ''during-SARS'' group . The nurses' levels of agreement with general SARS infection control measures and the need for quarantine after providing care for infected patients were significant predictors of nurses' commitment to their professional obligation. 2004 Gullion 14 20.2% of respondents were not at all willing to care for a patient infected with a communicable respiratory infection such as SARS.…”
Section: Resultsmentioning
confidence: 99%
“…13 Tam et al concurred with these findings and reported that nurses who had previously worked during an influenza public health emergency were less likely to avoid caring for patients with influenza. 23 Understanding the factors that might influence the HCP's willingness to report to work during an influenza epidemic is essential for preparedness planning. This review reveals various factors associated with a willingness to work during influenza emergency: being male, being a doctor or nurse, working in a clinical or emergency department, working full-time, prior influenza education and training, prior experience of working during an influenza emergency, the perception of value in response, the belief in duty, the availability of PPE, and confidence in one's employer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the issues will be to provide influenza vaccination to the public and especially to healthcare workers [1][2][3]. In this issue of Infection, Wicker et al [4] report about the compliance with influenza vaccination among healthcare workers.…”
mentioning
confidence: 99%